(untitled) (Baltic Journal of Sport and Health Sciences, 2026)
The promotion of sustainable physical activity (PA) increasingly necessitates participatory and co-creation methodologies that prioritise the involvement of citizens, stakeholders, and local authorities in the development and implementation of PA interventions. This symposium explores participatory approaches that empower individuals and communities to co-create environments and systems that foster active living, with a focus on equity, sustainability, and long-term impact. Five diverse contributions will present the application of participatory and co-creative approaches across various European contexts and population groups. The first presentation introduces a pioneering citizen science project in a low socio-economic neighbourhood in the Netherlands, where residents collaborated in the development of walking routes. The second presentation highlights the challenges and opportunities of co-creating supportive outdoor conditions, emphasising the importance of user-centred design and stakeholder collaboration in urban and rural planning. The third presentation provides insights from the WHO’s Health Economic Assessment Tool (HEAT) for walking and cycling. It illustrates how co-creation processes with diverse stakeholders can drive investment in active mobility by making the health and economic benefits visible and locally relevant. In the fourth presentation, the Placemaking & Sport project is examined across five European countries. It describes new ways of engaging communities in an active lifestyle to bring public space to life. The fifth presentation describes a case study at the municipality level on sustainable PA promotion for dementia prevention. The case study illustrates how, through a partly adapted cooperative planning approach and the establishment of community coordinator positions, the project successfully implemented evidence-based physical activity programmes across ten municipalities. Together, these presentations contribute to the growing body of evidence supporting participatory approaches in PA promotion. It offers critical insights into methodological considerations, contextual adaptations, and the implications for public health policy and practice. The symposium aims to inspire researchers, practitioners, and policymakers to embed co-creation and community engagement into all levels of PA promotion.